3(3x-9)=(x-3)

Simple and best practice solution for 3(3x-9)=(x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(3x-9)=(x-3) equation:


Simplifying
3(3x + -9) = (x + -3)

Reorder the terms:
3(-9 + 3x) = (x + -3)
(-9 * 3 + 3x * 3) = (x + -3)
(-27 + 9x) = (x + -3)

Reorder the terms:
-27 + 9x = (-3 + x)

Remove parenthesis around (-3 + x)
-27 + 9x = -3 + x

Solving
-27 + 9x = -3 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-27 + 9x + -1x = -3 + x + -1x

Combine like terms: 9x + -1x = 8x
-27 + 8x = -3 + x + -1x

Combine like terms: x + -1x = 0
-27 + 8x = -3 + 0
-27 + 8x = -3

Add '27' to each side of the equation.
-27 + 27 + 8x = -3 + 27

Combine like terms: -27 + 27 = 0
0 + 8x = -3 + 27
8x = -3 + 27

Combine like terms: -3 + 27 = 24
8x = 24

Divide each side by '8'.
x = 3

Simplifying
x = 3

See similar equations:

| 26+17+22+x/4 | | 9z-5c=30+c | | 5+4(5x-4)=7-3(2x+1) | | 5/6x-2/11x | | -a^2+11a=0 | | 5/6X+6/7-2/11X | | 2x+10+4(-x)=(-x)+(-20) | | 10d+5=7d+32 | | 2/5x+3=9 | | (1.49+0.59+0.49)=30.84+0.30 | | (7x-8)(3x+9)= | | fx=-1x+x^3 | | 4/5=c/7 | | 3-x-9+15x= | | 3x+(-2x)+x=3x+18 | | 3t+8=5t+8-2t | | 3(x-4)=-1.2 | | 100x-29=42671 | | 1/4x-1/8x=3-1/16x | | 60x=100 | | 7(a+2)=34.3 | | x*3=18 | | 0.25y-3.5=0.15y+1-0.8y | | 100x-29=100(426.71) | | -2/3x+2=6 | | 3(-2x+1)-4(-x)=-x+19 | | 3(-2x+1)-4(-x)=x+19 | | 3t+2(t+1)+7t+6=-16 | | 3x+6=3x-12 | | 7m-25=-32+6m | | z-42=-41 | | 20=5c-3 |

Equations solver categories